OPPOSITION TO RAIDING AS PART OF STATE ECONOMIC SECURITY POLICY - Меlnychenko O.A.; Pushkariova V.I. (Pressing Problems of Public Administration, 2015)
An overview of causes and consequences of raiding has been made. The essence of the concepts of ‘raiding’ and ‘opposition to raiding’ is specified. The classification of raiding counteraction components has been upgraded. Priority areas of implementing the state policy of economic security in the sphere are highlighted.